Clinical and treatment response differences according to age and gender in patients with acromegaly in Colombia: A retrospective study - Alin Abreu Lomba; Marcela Patiño Arboleda; Reynaldo Carvajal Ortiz; Nathalia Buitrago Gomez; Alejandro Pinzón Tovar; David Alexander Vernaza Trujillo; Alejandro Castellanos Pinedo; Rafael Castellanos Bueno; Doly Pantoja Guerrero; Henry Arenas Quintero (Revista Colombiana de Endocrinología, Diabetes y Metabolismo)
Context: Acromegaly is a rare disease characterized by excessive growth of bones and soft tissues due to hypersecretion of the growth hormone (GH), usually associated with pituitary tumors. Timely diagnosis and treatment are essential to reduce chronic complications.